2007
DOI: 10.1136/jcp.2007.052506
|View full text |Cite
|
Sign up to set email alerts
|

Expression of periostin in human breast cancer

Abstract: Results indicate that the aberrant gene expression of periostin in breast cancer cells is associated with an abnormal nuclear localisation of the protein. The nuclear localisation of periostin in breast cancer may induce significant biological effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
81
8
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(100 citation statements)
references
References 26 publications
10
81
8
1
Order By: Relevance
“…In breast cancer, Puglisi et al [48] reported a significant correlation between the expression of POSTN and VEGF-A and the VEGF-R1 and VEGF-R2 receptors. Similarly, Siriwardena et al [26] showed that in oral squamous-cell carcinoma (OSCC) blood vessel density of POSTN-positive tumors was higher than those of POSTN-negative tumors.…”
Section: The Role Of Periostin In Angiogenesis and Lymphangiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…In breast cancer, Puglisi et al [48] reported a significant correlation between the expression of POSTN and VEGF-A and the VEGF-R1 and VEGF-R2 receptors. Similarly, Siriwardena et al [26] showed that in oral squamous-cell carcinoma (OSCC) blood vessel density of POSTN-positive tumors was higher than those of POSTN-negative tumors.…”
Section: The Role Of Periostin In Angiogenesis and Lymphangiogenesismentioning
confidence: 99%
“…Increased expression of POSTN has been observed in various tumor types, including breast [44,48,[56][57][58], NSCLC [27,49,[59][60][61][62], colorectal [19,29,63], stomach cancers [64][65][66][67][68], pancreatic [32,69], prostate [70][71][72][73][74][75], ovarian cancer [76][77][78][79], and glioblastomas [80][81][82] (Table 1).…”
Section: Periostin Expression In Different Types Of Tumorsmentioning
confidence: 99%
“…Recent studies have shown that PN is highly expressed in various human cancers, and have suggested that PN promotes tumor growth and metastasis (3)(4)(5). Moreover, PN is believed to promote tumor growth and metastasis, and to be correlated with poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that periostin promotes adhesion and potentiates cancer cell motility by binding to integrins α ν β 3 and α ν β 5 (Gillan et al, 2002), and that forced expression of periostin induces invasive activity through epithelial-mesenchymal transition (EMT) in HEK-293 cells (Yan and Shao, 2006). Several studies correlate periostin expression with tumour angiogenesis and metastasis in human cancer Li et al, 2007;Malanchi et al, 2011;Puglisi et al, 2008;Sasaki et al, 2001aSasaki et al, ,b, 2003. Additionally, high pre-operative serum levels of periostin correlate with a poor prognosis in individuals with hepatocellular carcinoma after hepatectomy (Lv et al, 2013).…”
Section: Introductionmentioning
confidence: 99%